Analysis of Sustainability of Living Space of Orang Rimba in Taman Nasional Bukit Duabelas - Algopeng, Zozi; Irawan, Bambang; Suryono, Suryono (Program Pascasarjana Universitas Sriwijaya, 2023)
This study aims to analyze the sustainability status and analyze attributes sensitive to the sustainability status of Orang Rimba living space in the Taman Nasional Bukit Dua Belas (TNBD) area. The results showed that the sustainability status of Orang Rimba living space in the TNBD area in the ecological, economic, and institutional dimensions is quite sustainable, while socio-cultural is less sustainable. Multidimensional analysis of the sustainability of Orang Rimba living space in TNBD with an index of expert respondents and public respondents, both of which are categorized as unsustainable. Sensitive attributes of the ecological dimension include the suitability of Orang Rimba customary spaces with management zones, biodiversity management, and the suitability of Orang Rimba living activities. Sensitive attributes of the economic dimension include the potential of non-timber forest products, Orang Rimba's high expenditure, TNBD's direct benefits to Orang Rimba, and the market for non- timber forest products. Sensitive attributes of the socio-cultural dimension include Orang Rimba involvement in TNBD management, population growth, Orang Rimba education, local cultural practices, and trusting relationships among Orang Rimba. Sensitive attributes of institutional dimensions include the involvement of customary institutions in supervision and evaluation, stakeholder capacity, and mentoring of Orang Rimba